The Influence of Organizational Culture and Internal Communication on Employee Performance through Organizational Commitment as A Mediating Variable (A Case Study of Staff At Budi Luhur University) - Lalita Piktiora Faiza; Setyani Dwi Lestari (CV. Creative Tugu Pena, 2025)
This study aims to analyze the influence of Organizational Culture and Internal Communication on Employee Performance, with Organizational Commitment as a mediating variable among staff at Budi Luhur University. The study employed a quantitative approach using the SEM-PLS method through SmartPLS 4. The research population consisted of 447 employees, with a minimum sample of 82 respondents collected through a Likert-scale questionnaire. The findings indicate that Organizational Culture does not have a significant direct effect on Employee Performance, whereas Internal Communication has a significant effect on Employee Performance. Furthermore, both Organizational Culture and Internal Communication are proven to have a significant effect on Organizational Commitment. Organizational Commitment also has a significant effect on Employee Performance. The mediation test confirms that Organizational Commitment mediates the relationship between Organizational Culture and Employee Performance, as well as the relationship between Internal Communication and Employee Performance. Overall, the research model demonstrates strong explanatory power. These findings emphasize that improving employee performance can be optimized by strengthening internal communication and developing an organizational culture that fosters employee commitment.